2018
DOI: 10.1055/s-0038-1670707
|View full text |Cite
|
Sign up to set email alerts
|

Electric and Acoustic Stimulation in Cochlear Implant Recipients with Hearing Preservation

Abstract: Hearing loss affects 30 million people in the United States, and a subset of these patients have normal low-frequency hearing and ski-sloped high-frequency hearing loss. For these patients, hearing aids alone may not provide adequate benefit. Cochlear implantation alone has been utilized to improve speech perception. The addition of high-frequency electric hearing to low-frequency acoustic hearing in these patients is beneficial. Technical improvements have allowed preservation of low-frequency hearing in coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 125 publications
(165 reference statements)
0
16
0
Order By: Relevance
“…In terms of HP surgery, a round window approach is preferable as (1) less drilling reduces acoustic trauma, (2) it ensures insertion into the Scala tympani, and (3) preserves vestibular function [3], and we first clearly demonstrated that HP can be achieved even with the electrode beneath the basilar membrane [3]. In addition to the improved surgical approach, it is necessary to optimize the electrode array design.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In terms of HP surgery, a round window approach is preferable as (1) less drilling reduces acoustic trauma, (2) it ensures insertion into the Scala tympani, and (3) preserves vestibular function [3], and we first clearly demonstrated that HP can be achieved even with the electrode beneath the basilar membrane [3]. In addition to the improved surgical approach, it is necessary to optimize the electrode array design.…”
Section: Introductionmentioning
confidence: 92%
“…In such individuals who have severe-to-profound high-frequency HL with only mild-to-moderate HL in the low frequencies, hearing aids cannot offer any great benefit in terms of understanding speech. To address this issue, von Ilberg and colleagues developed the concept of electric-acoustic stimulation (EAS) providing low-frequency simulation via residual hearing together with electrical stimulation (ES) in the high frequencies by an inserted electrode in a single device [1,2]. The benefits of EAS in the implanted ear are well established and include improved speech recognition in noise compared with ES alone, indicating that the preservation of residual hearing in the low frequencies is important in EAS patients [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, fibrotic tissue and new bone formation constantly detected around the cochleostomy hole did not appear to impair CI outcome, except in the case of hybrid implants, and the lower density of neurons did not significantly reduce speech perception (4). Nonetheless, a thicker fibrous tissue within the cochlea may play a role in loss of residual hearing, and the preservation of low frequencies has a pivotal role in improving speech perception (44). In conclusion, the dexamethasone release is a good strategy to counteract the inflammatory reaction, but further studies on mechanisms underlying these side effects is essential to develop improved electrodes based on dexamethasone release that will be able to completely avoid the occurrence of inflammation.…”
Section: Discussionmentioning
confidence: 92%
“…This has given rise to the concept of hearing preservation (HP), which has been gradually refined. Several studies demonstrate that due to recent developments, including the round window insertion, slow insertion with lateral-wall electrodes and the application of intrascalar and systemic steroids, a high degree of HP is possible [3,12]. Regarding electrode design, thin, flexible, straight and shorter electrodes of 16, 20 and 24 mm in length were developed to minimize trauma during implantation and to cover the high-frequency range of the cochlea up to 1 kHz for ES [13].…”
Section: Discussionmentioning
confidence: 99%